KAJIAN RASIONALITAS PENGGUNAAN ANTIBIOTIK PADA PASIEN INFEKSI SALURAN KEMIH DI INSTALASI RAWAT JALAN RSUD ULIN BANJARMASIN - Nazhipah Isnani; Muliyani; Khairunnisa; Muhammad Zaini; Nabila Hadiah Akbar (Jurnal Insan Farmasi Indonesia, 2025)
Urinary Tract Infection (UTI) is in the second position as an infectious disease that often occurs in developing countries after infection in surgical wounds with a percentage of cases of 23.9%. Antibiotics are used as the main choice in the treatment of urinary tract infections, so there is a need for rational treatment measures in the use of antibiotic. Rational treatment can be achieved if it meets certain criteria. The aim of the research was determine the rationality of using antibiotik s in patients with urinary tract infections in the outpatient installation of Ulin Hospital, Banjarmasin. The research method used was descriptive quantitative with a cross sectional design using secondary data, namely medical records taken retrospectively. The results of the research carried out are that the highest use of antibiotic used to treat urinary tract infections in outpatients at Ulin Hospital Banjarmasin for the 2023 period is ciprofloxacin with a percentage of 52%, and the rationality of antibiotic based on the indication is 100% correct, the dose is 90% correct, the drug is 100% correct, the patient is 100% correct, the interval of administration is 90% correct, and the duration of administration is 90% correct.